A Critical Assessment of the Impact of GST on MSMEs in the state of Punjab - Dhillon, FCS Manjeet S; Gautam, RK (Gyan Management Journal, 2022)
On July 1, 2017, businesses in India had experienced a paradigm shift in the indirect taxation system, which integrated a large number of Central and State taxes into a uniform Goods and Services Tax (GST) law. GST has its Impact on every business across the industries. However, the impact on small & medium businesses has been more severe as compared to large ones. Therefore, MSME’s ability to withstand this significant tax & infrastructural reform needs to be studied in the light of their small scale & lower margins. In this regard, some pertinent queries need to be answered such as, how MSME has been impacted due to introduction of GST in terms of various costs such as cost of implementation, cost of compliances, as well as the cost of non-compliances etc likewise, challenges if any posed due to the development & alignment of new software systems with GSTN, training of human resources, and issues associated with the new accounting system.The research is significant as it strives to study multiple challenges being encountered such as the implementation cost, compliance/non-compliance costs, etc. among MSMEs in the state of Punjab as well as drafting recommendations and suggesting to the government and tax authorities in Punjab so that they could raise the voice and share the concern of Punjab’s MSME in the various GST Council meeting held from time to time. It is pertinent to mention and draw councils attention to increasing costs